2021
DOI: 10.1128/mcb.00660-20
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Biology of LRRK2 in Parkinson's Disease

Abstract: Point mutations in Leucine-rich repeat kinase 2 (LRRK2) are the most common cause of familial Parkinson’s disease (PD) and are implicated in a significant portion of apparently sporadic PD. Clinically, LRRK2-driven PD is indistinguishable from sporadic PD, making it an attractive genetic model for the much more common sporadic PD. In this review, we highlight recent advances in understanding LRRK2's subcellular functions using LRRK2-PD models, while also considering some of the limitations of these model syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 141 publications
0
40
0
Order By: Relevance
“…However, the role of GAK in the autophagy pathway has not been elucidated. Mutations in LRRK2 cause inherited Pd, and common variants around LRRK2 are risk factors for sporadic PD (67)(68)(69)(70). Genome-wide association studies have identified an SNP in GAK as a risk factor for sporadic Pd (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of GAK in the autophagy pathway has not been elucidated. Mutations in LRRK2 cause inherited Pd, and common variants around LRRK2 are risk factors for sporadic PD (67)(68)(69)(70). Genome-wide association studies have identified an SNP in GAK as a risk factor for sporadic Pd (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how LRRK2 functions and what goes wrong in disease-causing mutations will inform the rational design of specific LRRK2 inhibitors. Indeed, much effort has been directed at exploring the structure-function relationships in LRRK2 to gain a mechanistic understanding and guide the rational drug discovery (Usmani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Literature citations and REVEL scores [38] (http://database.liulab.science/dbNSFP) for each of the selected variants, as well as evolutionary conservation scores for each variant amino acid determined using the Consurf database (https://consurf.tau.ac.il/) [43], are tabulated in STable 1. The selected variants are located within the following domains: ARM (18), ANK (9), LRR (12), ROC (15), CORA (6), CORB (8), kinase (9) and WD40 (14) domains, as well as between the boundaries of the ANK and LRR (5), and LRR and ROC domains (2) (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%